La investigación del profesorado: aliada de la formación docente - Páez Martínez, Ruth Milena (Educación y Ciudad, 2020)
That the educational systems have focused their attention on students and learning left the importance of teachers in that same imbalance unbalanced. The pedagogical relationship, the learning of the teachers themselves and the research seem to have been located further from where they were. In this article, it is stated that teaching research is an important ally, not only to think about the teaching and learning of students, but also to update and rediscover the meaning of the same profession. Thus, it seeks to answer why teacher training necessarily involves teacher learning and why research motivates their desire to learn, while contributing to the development of dispositions and skills.